ETIKA GURU PAI DALAM PROSES PEMBELAJARAN MENURUT KITAB IHYA’ULUMUDDIN KARYA IMAM AL-GHAZALI - Intan Safitri; Khairuddin Khairuddin (KOLONI, 2022)
This research is motivated by education in Indonesia increasingly experiencing setbacks in terms of ethics both towards teachers, society, and other aspects of education. This causes educators to have an important role in character building and ethics as role models for students. So that the task of educators is not only to educate the mind, but to direct, guide, improve, purify themselves to get closer to Allah SWT. The process of humanizing humans from birth to the end of life is delivered in stages where the learning process is the responsibility of parents, the community and educators to become human beings. This research is a qualitative research with library research method, this research approach uses a descriptive analysis approach, namely by collecting, compiling and analyzing interpretations or interpretations in the Ihya'ulumuddin Book which discusses teacher ethics in learning to students. Data collection is done by reviewing related books and books to obtain more accurate information. The results of the study indicate that the Book of Ihya'ulumuddin by Imam Al-Ghazali shows how educators maintain their dignity towards students in the learning process and set an example to the prophet Muhammad SAW. So in the learning process there are criteria for teaching, including the results of research: 1) Teacher ethics in the learning process according to the Book of Ihya'ulumuddin by Imam Al-Ghazali. 2) the importance of maintaining the dignity of a teacher 3) The duties and responsibilities of teachers in education. 4) Al-Ghazali's thoughts are relevant to teacher ethics in the teaching and learning process. Keyword: Teacher Ethics, Ihya'ulumuddin Book, Imam Al-Ghazali